2013
DOI: 10.1007/s10461-013-0480-6
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening Adherence among HIV-Positive Female Smokers from a Comprehensive HIV Clinic

Abstract: HIV-positive women are at elevated risk for developing cervical cancer. While emerging research suggests that gynecologic health care is underutilized by HIV-positive women, factors associated with adherence to Pap testing, especially among HIV-positive female smokers are not well known. We utilized baseline data from a smoking cessation trial and electronic medical records to assess Pap smear screening prevalence and the associated characteristics among the HIV-positive female participants (n=138). Forty-six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…In view of an increased risk of malignancy, current guidelines recommend that HIV-infected women should undergo cervical cytological screening at least twice a year following an initial HIV diagnosis. In the event that both tests are normal, then annual screening needs to be conducted [8]. …”
Section: Introductionmentioning
confidence: 99%
“…In view of an increased risk of malignancy, current guidelines recommend that HIV-infected women should undergo cervical cytological screening at least twice a year following an initial HIV diagnosis. In the event that both tests are normal, then annual screening needs to be conducted [8]. …”
Section: Introductionmentioning
confidence: 99%
“…However, African American women living with HIV disease are less likely to adhere to the recommended screening intervals and follow-up on abnormal Pap test results. [25][26][27][28] Research suggests that factors such as older age, low educational attainment, lack of financial resources, and tobacco use are associated with lower cervical cancer screening among HIV-infected African American women. 25,[29][30][31] Studies have shown that the sociocultural environment influences the knowledge, beliefs, and values that influence decision-making associated with health behaviors such as participation in cervical cancer screening.…”
Section: Introductionmentioning
confidence: 99%
“…The integrated use of HPV testing remains controversial, and should not be used in women with abnormal pap tests. Participation in cervical cancer screening programs is low in HIV infected patients with low educational level, depressive symptoms, substance abuse, younger age and smoking, and efforts to increase screening are required 162 .…”
Section: Cancer Prevention Interventionsmentioning
confidence: 99%